Debirokratisasi dan Pentingnya “Good Governance” bagi Daerah - I Wayan Gede Suacana (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
The implementation of local governance involves not only the detachment from the shackles of central hegemony, the implementation of decentralization and regional autonomy policies, and the level of empowerment of civil society, but also attention to the ongoing conditions of the transition to democracy in people's lives in the region. Debureaucratization policy is one of the prerequisites for the implementation of good governance. The application of this policy requires the existence of a regional bureaucratic structure that can guarantee that there will be no distortion of aspirations coming from the community and avoid abuse of power. Debureaucratization requires that local governments can be more adaptive to changes and dynamics of society. Thus the bureaucracy will be more just and in favor of the sovereignty of the people so as to prioritize the interests of the people in a professional, proportionate and efficient manner. Debureaucratization practices and decentralization policies have become the main determinants that influence the dynamics of change for the realization of regional governance.